Toward adapting the UN’s healthy aging agenda for India: tailoring to unique historical context and traditions - Sastry, Nandakumar Bidare; Vempadapu, Monika; Sivananjiah, Shalini (Frontiers in Public Health, 2024)
India is known for its rich cultural heritage with different cultures and customs. Indian historical traditions and cultures were molded in a manner that most older adults were cared for at home by their children. However, India is being urbanized and developing swiftly changing its socio-cultural scenarios. With globalization and the increased popularity of social media, the youth is more ambitious than ever and is ready to migrate and explore. Fueled by the rapid aging of the global population, demand is escalating for robust programs, policies, and activities to improve the lives of older adults. However, most of these schemes have not yet been fully implemented nationwide; several state governments have yet to realize their full potential due to the lack of resources and competing priorities. Aligning with the UN’s healthy aging agenda, several programs and policies in India are contributing toward ensuring quality aged care services. This paper explores the challenges and opportunities for effective ground-level translation from precepts to practice.